Technology in Teaching English to Islamic Education Department Students at Indonesian Islamic University - Rosa, Vilentina (Universitas Pahlawan Tuanku Tambusai, 2024)
This research explores the incorporation of technology in instructing English to learners in the Islamic Education Department at Indonesian Islamic Universities. With the rise of globalization emphasizing the significance of English skills, it is crucial for these universities to implement creative teaching strategies that improve language acquisition. By conducting qualitative research that includes interviews and surveys with teachers and students, the study uncovers a range of technological resources—like language learning apps, digital platforms, and multimedia materials—that promote engaging and interactive learning settings. Results indicate that technology enhances engagement and accommodates various learning styles. Nonetheless, obstacles like insufficient technological infrastructure and differing degrees of digital literacy among educators and learners remain. This paper emphasizes the importance of professional growth and culturally appropriate content to successfully leverage technology's capabilities in enhancing English language learning within Islamic education settings. The findings highlight the pivotal impact of technology in enhancing the educational journey and equipping students for global interaction within an Islamic context.